Regulation of P-glycoprotein gene expression in hepatocyte cultures and liver cell lines by a trans-acting transcriptional repressor. - Gant, T W (1992)
Previously we have demonstrated that expression of the multidrug resistance (mdr) genes in rat liver and primary rat hepatocyte cultures is induced by exposure to 2-acetylaminofluorene and 3-methylcholanthrene. The mdr expression induced by both of these compounds occurs primarily via increased gene transcription. To determine the nature of possible regulatory proteins involved in mdr gene regulation we inhibited protein synthesis using cycloheximide or emetine in primary rat hepatocyte cultures, mouse (HePa 1), human (Hep G2) and rat (H4-II-E) cell lines. Each cell type responded by strongly increasing its steady state mdr1 mRNA levels. In hepatocytes increased mdr expression was observed after greater than 50% inhibition of protein synthesis, and was first detected after 2h of protein synthesis inhibition with maximal induction occurring by 24h. Nuclear run-on analysis showed that the increased steady state mRNA level was due to increased gene transcription without alteration of the transcription start site. Combined these data indicate that one regulatory mechanism by which mdr gene expression is controlled is via a trans-acting transcriptional repressor.